QEOSA: Testing a Pedagogical Model of Creative Problem Solving for Preschool Children. Issue 4 (2nd October 2021) - Cheng, Huai; Dai, David Yun; Yang, Panpan; Zhang, Jie; Cheng, Haoyu
ABSTRACT: Transfer, particularly far transfer through analogic mapping and reasoning, is considered one of the mechanisms for creative problem solving. However, the cognitive paradigm of training for analogical problem solving has not met with much success. It is argued by these authors that a pedagogical model that exclusively focuses on training for analogical mapping is not effective. In this study, an alternative pedagogical approach, QEOSA, standing for Question, Explore, Optimize, Show, and Act, was tested on analogical transfer of problem solving with preschool children. This pedagogical model was informed by the creativity research with respect to creative problem solving as soft constraint satisfaction, involving both divergent and convergent processes. A randomly assigned experiment with 221 preschool children was conducted using QEOSA for 4 months (one semester). The results provide evidence of effectiveness of QEOSA in promoting far transfer. Theoretical and practical implications of the study for building an effective pedagogy of creative problem solving are discussed.